Faculty Scholarship Celebration 2019 - Western Carolina University Hunter Library; Marcus, Elizabeth; Banerjee, Ruby; Roper, Elen; Roberson, Tony (2019)
Program and bibliography for Western Carolina University's annual Faculty Scholarship Celebration.